Outburst of the Spartakovskoye glacier-dammed lake and changes of the outlet glacier of the Semyonov-Tyan-Shansky Ice Cap, Severnaya Zemlya, in 2021 - A. Muraviev Ya.; R. Chernov A.; А. Муравьев Я.; Р. Чернов А. (Island Studies Journal, 2023)
In the second half of August 2021, outburst flood from the Spartakovskoe Lake, one of the largest glacierdammed lakes in the Russian sector of the Arctic, occurred on the Bolshevik Island (the Severnaya Zemlya archipelago). The lake hollow was drained. The volume of water discharged from the lake into the Spartak fjord was about 376 ± 21 mln. m3 . Only 5 years have passed since the last outburst of the lake in August 2016. The lake hollow was filled with water faster than in the period 2006–2016. The volume of runoff into the lake increased significantly due to more intensive surface ablation on the glaciers of the drainage basin during the anomalously warm summers in 2018–2021. For the up-floating of the ice dam restraining the lake overflowing, the height of the water edge in the lake before the outburst should have been about 113 m. Compared to the state of 2016, the maximum possible water level in the lake has dropped by about 10 m. That was a result of lowering of the glacier surface and, accordingly, a decrease in the thickness of the dam ice. The cartographic method was used to find a location of the area of the greatest depression of the dam surface, the occurrence was conditioned by the development of the under-ice runoff channel in 2016. It can be assumed that during the lake outburst in the second half of August 2021, its location was approximately the same as in 2016. The water level in the lake will no longer be able to rise to the watershed with the Bazovaya River basin (123 m). The flow from the lake to the Bazovaya River is now impossible. The glacial-dammed Lake Spartakovskoe is now a part of only the Kara Sea basin. Under the present-day climatic conditions, the surface of the ice dam decreases and, accordingly, the volume of runoff into the lake increases. In the future, this will probably result in more frequent outburst of the lake, a decrease in its volume, and accordingly, a reduction of the water volume discharging into the lake. Во второй половине августа 2021 г. на острове Большевик ...